Low-temperature curing one-component epoxy adhesive and preparation method thereof
Patent Information
- Application Number
- CN202610728553.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-26
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]本发明提供了一种低温固化单组份环氧胶黏剂及其制备方法,以解决当前胶黏剂无法满足LIPO工艺要求的技术问题
本发明采用硫醇固化剂替代传统胺类或酸酐类固化体系,其多巯基官能团在叔胺类或咪唑类促进剂协同催化下,能够在65℃的低温条件下与环氧基团快速发生开环加成反应,形成致密的三维交联网络结构,实现30分钟内完全固化,从根本上避免传统环氧胶黏剂120℃以上高温固化对手机屏幕及精密元器件造成的热损伤风险;采用固体三元丙烯酸树脂与纳米橡胶颗粒对环氧树脂基体进行共混改性,利用纳米橡胶颗粒以纳米级弹性微区形式均匀分散于树脂基体中,当胶层受到外力冲击时,弹性微区作为应力集中点能够有效诱发银纹并耗散冲击能量,从而大幅提升断裂伸长率和抗冲击性能;通过固体三元丙烯酸树脂分子链段的柔顺性调节基体刚性,优化树脂与橡胶相间的界面相容性,在提升韧性的同时保持胶体本身的高内聚强度,确保对屏幕、中框、排线等部件的牢固粘接;使得胶黏剂同时具备65℃低温快速固化、高强度粘接、高韧性抗开裂、优异耐候密封及良好工艺适配性的综合性能,有效解决传统环氧胶高温固化、韧性不足以及传统柔性胶粘接强度低的行业共性难题,完美适配LIPO低压真空注塑工艺对胶黏剂的严格要求。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of adhesive technology, and in particular to a low-temperature curing one-component epoxy adhesive and its preparation method. Background Technology
[0002] With the widespread adoption of full-screen smartphones, bezel widths are constantly shrinking, and traditional screen bonding processes can no longer meet the packaging requirements for ultra-narrow bezels (1.2mm). Low-injection pressure over-molding (LIPO) has emerged to address this need, enabling ultra-narrow bezel packaging, seamless bonding, and reliable sealing of precision components such as screen cables and mid-frames. The core material for this process is LIPO vacuum injection molding compound, which must simultaneously possess the functions of encapsulation, bonding, and sealing. It must not only firmly secure components such as the screen, mid-frame, and cables, but also meet waterproof and dustproof sealing requirements, and possess sufficient toughness to protect the screen from impacts and prevent cracking.
[0003] However, traditional PUR hot melt adhesives cannot simultaneously achieve both strong fixation and sealing in terms of process and performance; UV-curing adhesives require ultraviolet light penetration and cannot adapt to all process scenarios; epoxy adhesives typically have curing temperatures above 120°C, far exceeding the 80°C temperature resistance limit of components such as screens, and the adhesive is brittle and lacks toughness, easily causing screen cracking or bonding failure; traditional flexible adhesives generally have low bonding strength, making it difficult to firmly fix various components, and their weather resistance cannot meet long-term reliability requirements. Therefore, there is an urgent need to develop a new type of adhesive that can fully adapt to the requirements of LIPO processes. Summary of the Invention
[0004] This invention provides a low-temperature curing single-component epoxy adhesive and its preparation method to solve the technical problem that current adhesives cannot meet the requirements of the LIPO process.
[0005] In a first aspect, the present invention provides a low-temperature curing one-component epoxy adhesive, comprising the following raw material components in parts by weight: 100 parts of modified epoxy resin; 70-90 parts of thiol curing agent; 10 to 15 parts of curing accelerator; 30 to 80 parts of activated fused silica micro powder; 5 to 10 parts reactive diluent; 5 to 8 parts thixotropic agent; Stabilizer 3 to 5 parts; Carbon black 0.4 parts to 0.6 parts; The modified epoxy resin comprises a bisphenol A or bisphenol F epoxy resin matrix, and 10 wt% to 20 wt% solid ternary acrylic resin and 5 wt% to 15 wt% nano rubber particles dispersed in the matrix.
[0006] Optionally, the epoxy resin matrix is selected from bisphenol A type epoxy resin or bisphenol F type epoxy resin from Nan Ya Electronic Materials Co., Ltd.; the solid ternary acrylic resin is selected from Evonik Industries ELVACITE 4006; and the nano rubber particles are selected from S0207E from Yongqi Materials Technology (Shanghai) Co., Ltd.
[0007] Nano-rubber particles form elastic microdomains within the resin matrix, significantly improving the material's elongation at break and resistance to thermal shock. Ternary acrylic resins, through flexible molecular chain segment control and interface compatibility optimization, enhance the system's overall mechanical stability and long-term reliability.
[0008] In some of these embodiments, the modified epoxy resin is prepared by a method comprising the following steps: Nano-rubber particles were premixed with a portion of silane coupling agent to obtain a premix; The epoxy resin matrix and the remaining silane coupling agent were mixed at 80°C to 120°C, and the premix was added in batches under stirring. After high-speed dispersion and vacuum treatment, a mixture was obtained. Preheated and molten solid ternary acrylic resin is added to the mixture, stirred and mixed at 80℃~120℃, and then cooled to room temperature after vacuum treatment to obtain modified epoxy resin.
[0009] This embodiment ensures that the nano-rubber particles are uniformly dispersed in the epoxy matrix in a nanoscale elastic micro-region state after being premixed with a coupling agent and dispersed in batches at high temperature. At the same time, the addition of hot-melt ternary acrylic resin achieves full mutual solubility of molecular chain segments in the matrix, avoids agglomeration and phase separation, and ensures the microscopic uniformity of the modified system.
[0010] In some embodiments, the silane coupling agent is γ-glycidoxypropyltrimethoxysilane, and the total amount used is 2% of the mass of the nanoparticles. Its terminal epoxy groups participate in the curing reaction, and the alkoxy groups bond to the surface of the inorganic filler, significantly enhancing the interfacial bonding force between the resin matrix and the silica powder and the substrate, thereby improving the bonding strength and durability.
[0011] In some embodiments, the thiol curing agent is a polyfunctional thiol compound to enable the adhesive to cure rapidly at low temperatures and ensure long-term durability. Optional products include HSCURE 300 and HSCURE 200 from SC Organic Chemicals Co., Ltd.
[0012] In some embodiments, the curing accelerator is a tertiary amine or imidazole accelerator to lower the adhesive curing temperature and increase the curing speed, as well as increase the crosslinking density to improve durability. HSCHEM 1300 from Shanghai Hesheng Chemical Co., Ltd. is an option.
[0013] In some embodiments, the active fused silica powder comprises 10 to 20 parts of active fused silica powder with a particle size of 5 μm and 20 to 60 parts of active fused silica powder with a particle size of 10 μm. By using a blend of 5 μm and 10 μm particle sizes and optimizing the gradation to achieve close packing of the system, the curing shrinkage rate is effectively reduced and the dimensional stability of the material is improved. Simultaneously, it imparts appropriate flowability to the adhesive to meet the filling performance requirements of low-pressure injection molding processes.
[0014] In some embodiments, the reactive diluent is a low-viscosity glycidyl ether reactive diluent to effectively adjust the adhesive viscosity and improve its wettability and molding processability in a vacuum environment without impairing the mechanical properties of the system. ED-509S from Adico is an option.
[0015] In some embodiments, the thixotropic agent is hydrophobic fumed silica to give the adhesive good thixotropic properties, prevent sagging during injection molding, ensure accurate molding of the adhesive in complex mold cavities, and improve the mechanical strength and aging resistance of the system. Evonik R972 is optional.
[0016] In some embodiments, the stabilizer is barbituric acid, which improves the storage stability of the adhesive.
[0017] Secondly, the present invention also provides a method for preparing a low-temperature curing one-component epoxy adhesive, comprising the following steps: Add stabilizer and reactive diluent to the modified epoxy resin and stir until homogeneous; Add activated molten silica powder, thixotropic agent and carbon black, and continue stirring until homogeneous; Add thiol curing agent and curing accelerator, and continue stirring at 15℃~30℃ to obtain the adhesive compound; The obtained adhesive material is ground, vacuum degassed and filtered to obtain the low-temperature curing single-component epoxy adhesive.
[0018] Compared with the prior art, the present invention has the following beneficial effects: This invention uses a thiol curing agent to replace the traditional amine or anhydride curing system. Its multi-thiol functional groups, under the synergistic catalysis of tertiary amine or imidazole accelerators, can rapidly undergo ring-opening addition reactions with epoxy groups at a low temperature of 65℃, forming a dense three-dimensional cross-linked network structure, achieving complete curing within 30 minutes. This fundamentally avoids the risk of thermal damage to mobile phone screens and precision components caused by the high-temperature curing of traditional epoxy adhesives above 120℃. The invention also employs a blend modification of the epoxy resin matrix with solid ternary acrylic resin and nano-rubber particles. The nano-rubber particles are uniformly dispersed in the resin matrix in the form of nanoscale elastic micro-regions. When the adhesive layer is subjected to external impact, these elastic micro-regions act as stress concentration points, thus... It effectively induces silver crazing and dissipates impact energy, thereby significantly improving elongation at break and impact resistance. By adjusting the rigidity of the matrix through the flexibility of the solid ternary acrylic resin molecular chain segments, it optimizes the interfacial compatibility between the resin and rubber phases, improving toughness while maintaining the high cohesive strength of the colloid itself, ensuring a firm bond to components such as screens, mid-frames, and ribbon cables. This allows the adhesive to simultaneously possess comprehensive properties such as rapid curing at low temperature (65℃), high-strength bonding, high toughness and crack resistance, excellent weather resistance and sealing, and good process adaptability. It effectively solves the common industry problems of traditional epoxy adhesives' high-temperature curing and insufficient toughness, as well as the low bonding strength of traditional flexible adhesives, perfectly adapting to the stringent requirements of LIPO low-pressure vacuum injection molding process for adhesives.
[0019] Furthermore, this invention enables final mixing at room temperature, avoiding premature gelation, and ensures a uniform, bubble-free colloid through grinding and degassing, guaranteeing consistent adhesive performance and reliable application. It also simplifies production processes and improves efficiency. Simultaneously, this invention is a single-component epoxy adhesive, eliminating the need for complex mixing ratios before use. This effectively avoids performance fluctuations caused by mixing errors, reduces the risk of human error, and facilitates continuous industrial production. Detailed Implementation
[0020] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention are described in detail below. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0021] As used herein, the terms “prepared from” and “comprising” are synonymous. The terms “comprising,” “including,” “having,” “containing,” or any other variations thereof, as used herein, are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.
[0022] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, it should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. Unless otherwise specified, the raw materials used in the following examples and comparative examples are commercially available industrial products or prepared by conventional methods, and conditions not specifically stated are conventional conditions.
[0024] Example 1: Preparation of Modified Epoxy Resins 5% of the epoxy resin matrix nano-rubber particles (S0207E) and 1.5% of the nano-rubber particles by mass of KH560 silane coupling agent were premixed at 300 rpm for 1 h to obtain a premix. The epoxy resin matrix (Nanya Electronic Materials Co., Ltd.) and KH560 silane coupling agent (0.5% of the mass of nano-rubber particles) were dispersed at 1500 rpm for 30 min at 100 °C. The premix was added in 10 portions while stirring. After each addition, the mixture was stirred until the powder completely impregnated the resin. The mixture was then dispersed at 3000 rpm for 90 min. The vacuum degree was maintained at ≤-0.098 MPa and vacuumed for 30 min to obtain the mixture. Solid ternary acrylic resin (ELVACITE 4006), accounting for 10% of the epoxy resin matrix, was heated at 100°C for 2 hours to a molten state and then added to the mixture. The mixture was dispersed at 100°C and 3000 rpm for 60 minutes, and then vacuumed at a vacuum degree of ≤-0.098 MPa for 30 minutes. After cooling to 25°C, the modified epoxy resin was obtained.
[0025] Preparation Example 2 The difference from Preparation Example 1 is that the modified epoxy resin in Preparation Example 2 contains 15% solid ternary acrylic resin and 10% bisphenol A epoxy resin with nano rubber particles.
[0026] Preparation Example 3 The difference from Preparation Example 1 is that the modified epoxy resin in Preparation Example 3 contains 20% solid ternary acrylic resin and 15% bisphenol A epoxy resin with nano rubber particles.
[0027] Preparation Example 4 The difference from Preparation Example 1 is that the modified epoxy resin in Preparation Example 4 contains 10% solid ternary acrylic resin and 5% bisphenol A epoxy resin with nano rubber particles.
[0028] Table 1. Component dosage table for Examples 1 to 3
[0029] The preparation methods of the epoxy adhesives in Examples 1 to 3 include the following steps: Add stabilizer and reactive diluent to the modified epoxy resin and disperse at 1500 rpm for 15 min; Add activated molten silica powder, thixotropic agent and carbon black, and disperse at 1500 rpm for 15 min; Add thiol curing agent and curing accelerator, and disperse at 25°C and 1500 rpm for 30 min to obtain the adhesive; The obtained adhesive was ground twice using a three-roll mill, then vacuum degassed for 60 minutes at a vacuum degree of -0.098MPa and a dispersion speed of 1000rpm, and finally filtered through a 200-mesh filter to obtain a single-component epoxy adhesive. Example 4
[0030] The difference from Example 1 is that Example 4 uses the epoxy resin of Preparation Example 2 instead of the epoxy resin of Preparation Example 1. Example 5
[0031] The difference from Example 1 is that Example 5 uses the epoxy resin of Preparation Example 3 instead of the epoxy resin of Preparation Example 1. Example 6
[0032] The difference from Example 1 is that Example 6 uses the epoxy resin of Preparation Example 4 instead of the epoxy resin of Preparation Example 1.
[0033] Comparative Example 1 The difference from Example 4 is that Comparative Example 1 uses bisphenol A type epoxy resin instead of modified epoxy resin.
[0034] Comparative Example 2 The difference from Example 4 is that Comparative Example 2 uses a mixture of 90 parts of bisphenol A type epoxy resin and 10 parts of nano rubber particles dispersed at 1500 rpm for 30 min instead of modified epoxy resin.
[0035] Comparative Example 3 The difference from Example 4 is that Comparative Example 3 uses a mixture of 85 parts of bisphenol A type epoxy resin and 15 parts of solid ternary acrylic resin (molten state) dispersed at 1500 rpm for 30 min instead of modified epoxy resin.
[0036] Comparative Example 4 The difference from Example 4 is that Comparative Example 4 uses a mixture of 75 parts of bisphenol A type epoxy resin, 15 parts of solid ternary acrylic resin (molten state), and 10 parts of nano rubber particles dispersed at 1500 rpm for 30 min instead of modified epoxy resin.
[0037] Comparative Example 5 The difference from Example 4 is that the amount of thiol curing agent HSCURE 300 in Comparative Example 5 is 60 parts.
[0038] Comparative Example 6 The difference from Example 4 is that the amount of thiol curing agent HSCURE 300 in Comparative Example 6 is 90 parts, and the amount of curing accelerator HSCURE 1300 is 15 parts.
[0039] Comparative Example 7 The difference from Example 4 is that Comparative Example 7 has 5 parts of 5μm active fused silica powder and 30 parts of 10μm active fused silica powder.
[0040] Comparative Example 8 The difference from Example 4 is that Comparative Example 8 has 25 parts of 5μm active fused silica powder and 70 parts of 10μm active fused silica powder.
[0041] Performance testing 1. Viscosity test: The viscosity was tested using a Bollerfeld viscometer according to GB / T 15357-2014 standard, with a rotor of 52 oz and a rotation speed of 1 rpm.
[0042] 2. Thixotropic test: According to GB / T 5561-1994 standard, the test temperature is 25±1℃.
[0043] 3. Hardness test: According to GB / T 2411-2008 standard, the test temperature for hardness is 25±2℃.
[0044] 4. Shear strength test: According to GB / T 7124-2008 standard, the test temperature for shear strength is 25±2℃. The curing temperature and time for each substrate sample is 65℃ for 30 minutes.
[0045] 5. Tensile strength and elongation at break tests: in accordance with GB / T 2568-1995 standard, the test temperature is 25±1℃.
[0046] 6. Ball drop test: Cover 1mm of glass (tempered glass) with 1mm of adhesive, drop a 100g SUS ball from a height of 40cm three times; cover 1mm of glass (tempered glass) with 1mm of adhesive, drop a 200g SUS ball from 40cm three times (record the actual number of cracks).
[0047] 7. Thermal shock test: -40℃ to 85℃. After storing at -40℃ for 2 hours, switch to 85℃ for 2 hours. The switching interval should not exceed 1 minute.
[0048] Table 2 Performance test results of Examples 1 to 6
[0049] Table 3 Performance test results of Comparative Examples 1 to 4
[0050] Table 4 Performance test results of comparative examples 5 to 8
[0051] As shown in Tables 2-3, the low-temperature curing single-component epoxy adhesive prepared by this invention, through the specific ratio of modified epoxy resin and other components (HSCURE 300, HSCEM1300, barbituric acid, KH560, R972, activated fused silica powder, carbon black, etc.) and combined with an optimized preparation process, exhibits significant advantages in various properties. For example, compared with Comparative Examples 1-4, Example 4 shows significant improvements in shear strength (aluminum alloy to aluminum alloy, PC to PC, PET to PET, PMMA to PMMA), tensile strength, elongation at break, low-pressure vacuum injection molding effect, ball drop effect, and shear strength after double 85mm and thermal shock. Especially in the low-pressure vacuum injection molding effect, Example 4 achieves no sagging, good molding, and demolding, while Comparative Example 1 suffers from sagging, poor molding, and demolding cracking problems, and Comparative Examples 2 and 4 have problems such as high viscosity leading to slow injection flow speed and corner voids. In the drop test, the 100g ball of Example 4 withstood 3 drops without cracking after 4 drops, and the 200g ball withstood 3 drops without cracking after 4 drops, which is far better than the performance of the comparative example, which cracked after only 1-2 drops. Clearly, this invention can meet the requirements of low-pressure vacuum injection molding processes for high strength, high toughness, and rapid low-temperature curing of adhesives.
[0052] As shown in Tables 2 and 4, compared with Example 4, Comparative Example 5 reduced the amount of HSCURE 300, resulting in a curing time extended to 45 minutes. Simultaneously, mechanical properties such as shear strength and tensile strength decreased, and the drop performance of the small balls also deteriorated. Comparative Example 6 increased the amounts of HSCURE 300 and HSCEM1300. Although the curing time was shortened to 20 minutes, the thixotropic value decreased, sagging was more severe, and the elongation at break decreased significantly. Comparative Example 7 reduced the amounts of R972 and 5µm active fused silica powder, and increased the amount of 10µm active fused silica powder, resulting in a decreased thixotropic value, more severe sagging, and adverse effects on shear strength and tensile strength. Comparative Example 8 increased the amount of R972, significantly increased the amount of 5µm active fused silica powder, and reduced the amount of 10µm active fused silica powder, resulting in a significant increase in viscosity, slow injection flow rate, severe voids at corners, and a significant decrease in elongation at break. Clearly, the specific proportions of each component in this invention are key to ensuring the superior overall performance of the adhesive.
[0053] 1. Low-temperature rapid curing, reducing process energy consumption and equipment requirements: The adhesive of this invention can cure within 30 minutes at 65℃, far lower than the curing temperature of traditional epoxy adhesives above 120℃, effectively avoiding the potential damage risk of high temperatures to mobile phone screens and internal precision components (which typically have a temperature resistance below 80℃). At the same time, low-temperature curing significantly reduces energy consumption costs in the production process, simplifies process conditions, and correspondingly reduces the high-temperature resistance requirements of production equipment, which is conducive to saving production costs and improving production efficiency.
[0054] 2. A perfect combination of high strength and high toughness enhances bonding reliability: Through specific resin modification (containing solid ternary acrylic resin and nano rubber particles), the adhesive of this invention, after curing, not only has extremely high shear strength, which can firmly fix key components such as screen, mid-frame, and ribbon cable, and meet the sealing requirements for waterproofing and dustproofing; but also has excellent toughness and elongation at break, which can effectively absorb external impact energy, significantly reduce problems such as screen cracking and bonding failure caused by brittleness of the adhesive or stress concentration, and greatly improve the structural reliability of smartphones in daily use and accidental drop conditions.
[0055] 3. Excellent weather resistance, ensuring long-term stability: Through the synergistic effect of its components, particularly the selection and optimization of curing agents, accelerators, and stabilizers, the adhesive of this invention possesses excellent weather resistance. After a 7-day test in an environment of 85°C and 85% relative humidity, its shear strength remains at a high level, ensuring the long-term bonding stability and reliability of the adhesive in the complex usage environment of smartphones (such as temperature changes and humidity effects), thus extending the product's service life.
[0056] 4. Excellent process adaptability to meet the requirements of LIPO low-pressure vacuum injection molding: The adhesive of this invention, through the optimization of the gradation of active fused silica micropowder, the addition of diluents, and the application of fumed silica as a thixotropic agent, possesses suitable viscosity and excellent thixotropic properties. This not only ensures that the adhesive has good flowability and filling properties during low-pressure vacuum injection molding, enabling precise molding in complex mold cavities and avoiding sagging, but also ensures the dimensional stability of the colloid after injection molding. It is perfectly compatible with the LIPO low-pressure vacuum injection molding process widely used in modern electronics manufacturing, providing strong technical support for the design of precision structures such as ultra-narrow bezels.
[0057] 5. Single-component system, simplified production process: This invention is a single-component epoxy adhesive, which eliminates the need for complex mixing and formulation before use, effectively avoiding performance fluctuations that may be caused by formulation errors. At the same time, it simplifies the production process, improves production efficiency, reduces the risk of human error, and is more conducive to continuous industrial production.
[0058] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0059] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the scope of protection of the present invention. In particular, it should be noted that any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention for those skilled in the art.
Claims
1. A low-temperature curing one-component epoxy adhesive, characterized in that, Includes the following raw material components by mass: 100 parts of modified epoxy resin; 70-90 parts of thiol curing agent; 10 to 15 parts of curing accelerator; 30 to 80 parts of activated fused silica micro powder; 5 to 10 parts reactive diluent; 5 to 8 parts thixotropic agent; Stabilizer 3 to 5 parts; Carbon black 0.4 parts to 0.6 parts; The modified epoxy resin comprises a bisphenol A or bisphenol F epoxy resin matrix, and 10 wt% to 20 wt% solid ternary acrylic resin and 5 wt% to 15 wt% nano rubber particles dispersed in the matrix.
2. The low-temperature curing one-component epoxy adhesive as described in claim 1, characterized in that, The modified epoxy resin is prepared by a method comprising the following steps: Nano-rubber particles were premixed with a portion of silane coupling agent to obtain a premix; The epoxy resin matrix and the remaining silane coupling agent were mixed at 80°C to 120°C, and the premix was added in batches under stirring. After high-speed dispersion and vacuum treatment, a mixture was obtained. Preheated and molten solid ternary acrylic resin is added to the mixture, stirred and mixed at 80℃~120℃, and then cooled to room temperature after vacuum treatment to obtain modified epoxy resin.
3. The low-temperature curing one-component epoxy adhesive as described in claim 2, characterized in that, The silane coupling agent is γ-glycidoxypropyltrimethoxysilane, and the total amount used is 2% of the mass of the nanoparticles.
4. The low-temperature curing one-component epoxy adhesive as described in claim 1, characterized in that, The thiol curing agent is a multifunctional thiol compound.
5. The low-temperature curing one-component epoxy adhesive as described in claim 1, characterized in that, The curing accelerator is a tertiary amine or imidazole accelerator.
6. The low-temperature curing one-component epoxy adhesive as described in claim 1, characterized in that, The active fused silica micro powder comprises 10 to 20 parts of active fused silica micro powder with a particle size of 5 μm and 20 to 60 parts of active fused silica micro powder with a particle size of 10 μm.
7. The low-temperature curing one-component epoxy adhesive as described in claim 1, characterized in that, The reactive diluent is a low-viscosity glycidyl ether reactive diluent.
8. The low-temperature curing one-component epoxy adhesive as described in claim 1, characterized in that, The thixotropic agent is hydrophobic fumed silica.
9. The low-temperature curing one-component epoxy adhesive as described in claim 1, characterized in that, The stabilizer is barbituric acid.
10. A method for preparing a low-temperature curing one-component epoxy adhesive as described in any one of claims 1 to 9, characterized in that, Includes the following steps: Add stabilizer and reactive diluent to the modified epoxy resin and stir until homogeneous; Add activated molten silica powder, thixotropic agent and carbon black, and continue stirring until homogeneous; Add thiol curing agent and curing accelerator, and continue stirring at 15℃~30℃ to obtain the adhesive compound; The obtained adhesive material is ground, vacuum degassed and filtered to obtain the low-temperature curing single-component epoxy adhesive.